OPTIMASI PROSES DAN STUDI KINETIKA PADA SINTESA BIODIESEL DARI USED COOKING OIL BERBASIS CRUDE PALM OIL (CPO) DENGAN REAKSI ETANOLISIS - , PUTRI RESTU DEWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In recent year, biodiesel has attracted significant attention from researchers, goverment and industries as a renewable energy, biodegradable, and non-toxic fuel. However, several feedstock have been profen impractical or infeasible because of their extremely high cost due to their usage primarily as food resource. Used cooking oil is considered the most promising low-cost feedstock for biodiesel production. While ethanol produced from agricultural renewable resources can be used as reactant of the process, instead of methanol which is from non renewable resource. This research is aimed to study production of biodiesel from used cooking oil as low-cost feed stock and ethanol as renewable resource. Synthesis of biodiesel was carried out in a 500 mL spherical reactor, provided with a thermometer, mechanical stirring, sampling outlet, and condensation systems. The 150 g of used cooking oil was mixed with ethanol and catalyst that have been mixed and preheated first until the temperature same with the used cooking oil. The sample was take every 15 minutes and being analysis to determine the presence of total glycerol and free glycerol. The operation variables employee were ethanol/oil molar ratio (4:1-12:1), catalyst concentration (1.1-1.5 wt.%), temperature (40-70 0C) and stirrer velocity (200-500 rpm) . Oil mass (150 g), reaction time (150 minutes) and alcohol type (ethanol) were fixed as common parameters in all experiments. The highest conversion Â±96.5 % was achieved in the reaction with temperatur 70 0C, catalyst concentration 1,5 wt.%, ethanol/oil ratio 9:1 and stirrer velocity 500 rpm. Kinetic study was evaluated with approachment heterogeneous reaction between oil and ethanol. Study was concerned in the effect of mass transfer and chemical reaction. The proposed kinetic model and the experimental data show a good agreement. Activation energy of 4.236 J/mol in forward reaction was obtained in the range temperature of 40-70 0C. Hatta number was determined 0,02>MH>2 that means both mass transfer and reaction velocity influence the process in the range temperature of 40-70 0C and stirrer velocity 200-500 rpm.